Why More Prevalence of Thyroid Disorders in Women in Present Scenario (AYUSHDHARA, 2023)
It is no surprise that women nowadays face a slew of health challenges. Thyroid dysfunctions, which are primarily caused by an imbalance of thyroid hormones are growing more frequent, with the American Thyroid Association estimating that one out of every eight women may experience thyroid challenges over her lifetime. Furthermore, it is expected that women are 5 to 8 times more prone than males to acquire thyroid issues. Because of modernity and increased stress in everyday life, Vega dharana, hormonal changes, iodine insufficiency, auto-immune disorders resulting in numerous endocrinal disorders in females. Hypothyroidism and hyperthyroidism is a prevalent endocrine illness that affects people all over the world. These figures point to an increase in the number of women experiencing health issues such as menstrual cycle imbalance, polycystic ovarian syndrome, sudden weight gain or loss, hypertension, lethargy, dry skin and hair, constipation and so on, all of which have their own effects on the body and are directly or indirectly related. The review will be useful in understanding the pathophysiology of Thyroid disorders and changing the disease's treatment regimen.